ANALISIS DISPARITAS PENDAPATAN ANTAR WILAYAH DI PROVINSI JAMBI (PENDEKATAN ENTROPY THEIL INDEKS) - Siti Aminah (Universitas Batanghari Jambi, 2017)
This research aims to know the economic growth of the kabupaten/kota in Jambi province and to find out the economic gaps between areas in Jambi province by using the index and the Theil Entropy model using data GDP as well as the total population of the year 2011 till the year 2015. The results obtained on a regional basis the rate of development of GDP experienced a fluctuation of the years 2011 to 2015 average of 6.79%. During the period that shows the rate of economic growth was the highest average of Sarolangun Regency 7.43%. Theil Entropy of the approach over a period of years 2011 to 2015 year average index of inequalities between different areas in Jambi province is 0.426 this value indicates the index of the gap. Keyword: income disparity, economic growth